Trends in International Collaboration and Citation Impact in Life Insurance Mathematics and Economics: A Bibliometric Analysis - Rahul Gedamkar, Pallavi; Thite, Ajit (Journal of Neonatal Surgery, 2025)
This study provides a comprehensive bibliometric analysis of research trends in the field of insurance mathematics and economics from 2014 to 2023. Using data from two primary sources, Insurance: Mathematics and Economics and Geneva Papers on Risk and Insurance: Issues and Practice, we examine patterns of international collaboration, citation impact, and author productivity. The analysis reveals a decline in annual growth rate (-25.37%) but highlights significant contributions from countries such as Germany, China, and the USA. The study also identifies key authors, institutions, and documents that have shaped the field, offering insights into the dynamics of research productivity and collaboration.